2011
DOI: 10.3109/07357907.2010.543210
|View full text |Cite
|
Sign up to set email alerts
|

Human Beta-Defensin-1, -2, and -3 Exhibit Opposite Effects on Oral Squamous Cell Carcinoma Cell Proliferation

Abstract: The objective of this study was to investigate the impact of human beta-defensins (hBDs) on oral squamous cell carcinoma (OSCC) proliferation and hBD expression in vitro. BHY-OSCC cell lines were stimulated with hBD-1, -2, and -3. Proliferation of BHY cells was ascertained and hBD-mRNA expression was evaluated by real-time PCR. Proliferation of BHY cells decreased by 25% in response to hBD-1 stimulation but increased after stimulation with hBD-2 and -3. HBD-1 stimulation enhanced hBD-3 expression, whereas HBD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 19 publications
2
58
3
Order By: Relevance
“…The inconsistency between our findings compared to those from previous investigations reporting that tumors overexpressing hBD3 or Defb14 showed enhanced solidtumor growth remains unclear (14,15,27). This may have occurred because of differences in the concentration of hBD3 and Defb14 used, although the concentration of 20 μg/ml defensin used in our study was not excessively higher than that at which antimicrobial activity was observed (10).…”
Section: Figure 3 Time Dependency Of Cellular Damage Induced By Humacontrasting
confidence: 56%
See 1 more Smart Citation
“…The inconsistency between our findings compared to those from previous investigations reporting that tumors overexpressing hBD3 or Defb14 showed enhanced solidtumor growth remains unclear (14,15,27). This may have occurred because of differences in the concentration of hBD3 and Defb14 used, although the concentration of 20 μg/ml defensin used in our study was not excessively higher than that at which antimicrobial activity was observed (10).…”
Section: Figure 3 Time Dependency Of Cellular Damage Induced By Humacontrasting
confidence: 56%
“…Some studies hypothesized that hBD3 can be oncogenic because hBD3 is frequently overexpressed in oral squamous cell carcinomas (13)(14)(15). Winter et al indicated that hBD3 inhibited colon cancer-cell migration, although not cell proliferation (16).…”
mentioning
confidence: 99%
“…Additionally, hBD-2 has a strong impact on the maturation of premature osteoblasts [15]. Furthermore, hBD-1, -2, and -3 have been demonstrated to stimulate the proliferation of tumor cells in vitro [16] (Figure 4). Apart from that, the gene products of human β-defensins cross-regulate their own gene expression [15,16].…”
Section: Tissue Reorganization and Wound Healingmentioning
confidence: 99%
“…Recently, it has been demonstrated that human β-defensins are involved in bisphosphonate-associated osteochemonecrosis of the jawbone [13]. Furthermore, these antimicrobial peptides are able to affect their own genes-either directly or indirectly by modulating gene activity and secretion of cytokines, which in consequence leads to feedback mechanisms on defensin genes [4,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation